2015
DOI: 10.3354/meps11092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copepod size on fish growth: a model based on data for North Sea sandeel

Abstract: In productive marine off-shore ecosystems, the flow of energy from zooplankton to large predators is channeled through a few species of short-lived, highly abundant schooling planktivorous fish. There are indications that these species respond to qualitative and phenological changes in the zooplankton. If so, the climate-induced alterations of the local copepod communities that we see in temperate and arctic regions may influence the energy flux in marine food chains. In order to investigate how different proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…The substantial downward shift in key elements of the plankton (McQuatters-Gollop et al, 2007;Pitois & Fox, 2006) and stock production across a range of zooplanktivorous species (results presented here), seem to indicate a declining primary production (Ware & Thompson, 2005). However, other studies point to changes in zooplankton species composition as the cause of reduced fish growth (Beaugrand et al, 2003;Van Deurs, Jørgensen, & Fiksen, 2015). Factors such as spawning site diversity or the frequency of unlikely events governing extreme recruitment outburst (Lowerre-Barbieri et al, 2016;Pepin, 2015) have also been proposed as drivers of variation in fish stock production.…”
Section: Discussionmentioning
confidence: 99%
“…The substantial downward shift in key elements of the plankton (McQuatters-Gollop et al, 2007;Pitois & Fox, 2006) and stock production across a range of zooplanktivorous species (results presented here), seem to indicate a declining primary production (Ware & Thompson, 2005). However, other studies point to changes in zooplankton species composition as the cause of reduced fish growth (Beaugrand et al, 2003;Van Deurs, Jørgensen, & Fiksen, 2015). Factors such as spawning site diversity or the frequency of unlikely events governing extreme recruitment outburst (Lowerre-Barbieri et al, 2016;Pepin, 2015) have also been proposed as drivers of variation in fish stock production.…”
Section: Discussionmentioning
confidence: 99%
“…Adult anchovies of the Bay of Biscay feed primarily in offshore habitats (Chouvelon et al, 2014) but Pasquaud et al (2008) observed that small anchovies can also feed along with sprats in estuarine habitats of the Gironde. If competition between the three species occurs in the Gulf of Lions, sprats should have an advantage considering their larger niche width, the feeding on slightly larger, and thus, more energetic prey (Gerking, 1994;van Deurs et al, 2015) than anchovies and sardines, their lowest predator/prey size ratios and because they seem to recover well after the spawning period (Pethybridge et al, 2014).…”
Section: Interaction Between Planktivorous Teleost Speciesmentioning
confidence: 98%
“…Here, higher SSTs did not affect recruitment, but were associated with lower SSB and TSB. Sandeels face greater metabolic costs at higher temperatures and under these conditions their prey may be less abundant (van Deurs, Koski, & Rindorf, 2014;van Deurs et al, 2011), leading to slower growth, reduced maturation, reduced reproductive investment, increased overwintering weight loss, and reduced survival (Heath et al, 2012;van Deurs, Jørgensen, & Fiksen, 2015;van Deurs et al, 2009;Wright, Orpwood, & Scott, 2017). However, whilst expected impacts of high temperatures on sandeels were observed, impacts on kittiwakes appeared more complex.…”
Section: Environmental Effectsmentioning
confidence: 99%